Pendapat Auditor atas Laporan Keuangan untuk Perusahaan yang Terdaftar di Bursa Efek Jakarta - Antonius Herusetya (Bina Nusantara University, 2007)
Reports are essentials to audit and assurance engagements because they communicate the result of auditor’s findings. The reason for this research is to study what types of the audit report has been issued for listed public companies in Bursa Efek Jakarta (BEJ). Audited reports from 106 sample companies are examined. Our findings reveal that most of the audit opinion among listed companies in Indonesia is unqualifed opinion (51.89%), followed by unqualified opinion with explanatory paragraph (39.79%), qualified opinion (7.55%), and disclaimer opinion (3.77%). Each audit opinion has its own condition that varies among many companies.